The becoming [large type] - Roberts, Nora (Roberts, Nora. Dragon heart legacy, 2021)
"The world of magick and the world of man have long been estranged from one another. But some can walk between the two -- including Breen Siobhan Kelly. She has just returned to Talamh, with her friend, Marco. In Talamh, Breen is learning to embrace the powers of her identity. Marco is welcomed kindly by her people -- and by Keegan, leader of the Fey. But one member of Breen's bloodline is not there to embrace her. Her grandfather plots to destroy Talamh -- and now all must unite to defeat his dark forces. There will be betrayal and bloodshed. But through it, Breen will take the next step on the journey to becoming all that she was born to be"--